Effect of vitamin K1 supplementation on left colon healing in rats with extrahepatic biliary obstruction - Amaral,Maria Eduarda Bonavides (2014)
PURPOSE:To evaluate the effects of vitamin K1 on wound healing in the left colon of rats with experimental biliary obstruction.METHODS: Sixteen male rats, divided into four groups of four animals each (L, M, LK, and MK), underwent colostomy followed by bowel suture in the left colon. Seven days before, animals in the L and LK groups had undergone common bile duct ligation. The animals in groups MK and LK received vitamin K1 supplementation. On day 7 after bowel suture, repeat laparotomy was performed for evaluation of colonic healing by burst pressure measurement and collection of samples for histopathological analysis. Changes in body weight were evaluated in the four groups.RESULTS:Weight loss was lower in animals supplemented with vitamin K. No significant differences were observed in burst pressure among the four groups (p>0.05). Histological analysis showed more hemorrhage and congestion in the biliary obstruction groups. Supplemented animals exhibited increased collagen formation and less edema and abscess formation.CONCLUSION:Vitamin K supplementation attenuated weight loss and improved colonic wound healing in rats.